Evaluating technical vocational education and training college student’s digital skills versus throughput rate - Goodwill Phezulu Mbambo; Elizabeth C. du Plessis (Discover Education)
Abstract The lack of digital skills among Technical Vocational Education and Training (TVET) college students is a challenge that negatively affects their academic performance, leading to the college’s poor throughput rate. This study aimed to evaluate the digital skills and knowledge of TVET college students of Newcastle, South Africa, about their throughput rate. This is achieved by examining their ability to apply digital skills to succeed in their academic quest. Digital skills are now characterised by globalisation, digitisation, robotics, Artificial Intelligence (AI), big data, the Internet of Things (IoT), and various other emerging technologies consuming the world. The study employed a descriptive quantitative approach, where respondents completed a four-point Likert scale questionnaire for data collection. The student’s assessment records were explored to establish the college throughput rate. Data were descriptively and inferentially analysed by using Microsoft Excel. The relationship between the TVET college’s low throughput rate and students’ lack of digital skills was statistically significant. An existing digital skills gap calls for educational institutions to equip students with modern and innovative technology-related skills to enhance the throughput rate.